2016
DOI: 10.1177/2325967116673560
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Novel Weightbearing Cone Beam Computed Tomography Scanner Versus a Conventional Computed Tomography Scanner for Measuring Patellar Instability

Abstract: Background:Conventional computed tomography (CT) images are routinely used for diagnosing patellofemoral instability and are obtained with the patient in a supine position, nonweightbearing, with the knee in full extension, and with leg muscles relaxed. A new portable extremity cone beam CT (CBCT) scanner has been developed that may allow for more accurate diagnosis, as imaging can be performed with the patient standing, the knee flexed, and with leg muscles active.Purpose/Hypothesis:The purpose of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…Spatial resolution permits visualization of ~0.25–0.35 mm high‐contrast features (frequency at 10% of the modulation transfer function, f 10 , approximately 1.5–1.8 mm −1 ), yielding improved visualization of bone detail compared to MDCT . A compact gantry with flexible positioning capability permits weight‐bearing imaging of lower extremities in addition to nonweight‐bearing acquisitions, providing new insight in weight‐bearing evaluation of areas such as osteoarthrtis (OA), patellar malformation, and flatfoot deformity…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial resolution permits visualization of ~0.25–0.35 mm high‐contrast features (frequency at 10% of the modulation transfer function, f 10 , approximately 1.5–1.8 mm −1 ), yielding improved visualization of bone detail compared to MDCT . A compact gantry with flexible positioning capability permits weight‐bearing imaging of lower extremities in addition to nonweight‐bearing acquisitions, providing new insight in weight‐bearing evaluation of areas such as osteoarthrtis (OA), patellar malformation, and flatfoot deformity…”
Section: Introductionmentioning
confidence: 99%
“…Scan dose is 5-15 mGy, the field-of-view (FOV) is 20 9 20 9 20 cm 3 , and typical scan time is~30 s. 3 Spatial resolution permits visualization of~0.25-0.35 mm high-contrast features (frequency at 10% of the modulation transfer function, f 10 , approximately 1.5-1.8 mm À1 ), yielding improved visualization of bone detail compared to MDCT. 4,5 A compact gantry with flexible positioning capability permits weight-bearing imaging of lower extremities in addition to nonweight-bearing acquisitions, providing new insight in weight-bearing evaluation of areas such as osteoarthrtis (OA), [6][7][8] patellar malformation, 9 and flatfoot deformity. 10 The high spatial resolution motivates application of extremity CBCT in quantitative imaging of bone microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional CT scans of the knee are acquired with the patient in a supine, nonweightbearing position, but limitations of this technique have been reported. 16 , 22 New CT systems, including the On-Sight cone-beam CT scanner (Carestream Health), are available to acquire images while the patient is standing and to allow various positions of knee flexion and extension. 11 , 22 , 33 It has been shown that knee position and weightbearing can independently affect the TT-TG offset distance.…”
mentioning
confidence: 99%
“… 16 , 22 New CT systems, including the On-Sight cone-beam CT scanner (Carestream Health), are available to acquire images while the patient is standing and to allow various positions of knee flexion and extension. 11 , 22 , 33 It has been shown that knee position and weightbearing can independently affect the TT-TG offset distance. 2 , 12 , 16 , 22 , 32 , 37 …”
mentioning
confidence: 99%
“…For decades, radiographic measurements of the foot and knee bones have been proposed, investigated, applied, and discussed. 11,16,[40][41][42] These include single-bone absolute orientation, interbone relative alignments, distances, arch angles, and also morphological aspects of the single bones. A recent literature review 43 surveyed the most popular of these foot and ankle radiographic measures, although they are still based on weight-bearing radiographic images.…”
Section: Discussionmentioning
confidence: 99%